Taking it to the streets: Teaching public scholarship strategies for community impact and student success - Hall, Robyn (My University, 2023)
Higher education’s expanding focus on community-based research is opening up new opportunities for students to develop and apply literacy skills that can have real world impact. This session will discuss several strategies librarians can use to teach students about creating and sharing research outputs intended for use by community partners and the broader public, with a focus on accessibility, knowledge equity and knowledge mobilization. Participants will be encouraged to reflect on their own instruction and ways that they can expand their teaching to incorporate public scholarship strategies to benefit students creating and sharing works beyond the classroom.
Presented on May 18, 2023 at the Workshop for Instruction in Library Use (WILU) Conference held at McGill University in Montreal, Quebec.
Keywords: community-based research; undergraduate research; academic libraries; information literacy; public scholarship